Assessing the views and opinions of psychiatric patients receiving genome-guided treatment within the scope of the PREPARE preemptive pharmacogenomics clinical study - Koufaki, Margarita-Ioanna; Pandi, Maria-Theodora; Skokou, Maria; Karamperis, Kariofyllis; Vasileiou, Konstantinos; Mitropoulou, Christina; Williams, Marc S.; Patrinos, George P. (Frontiers in Pharmacology, 2025)
IntroductionPharmacogenomics (PGx), an essential component of Personalized Medicine (PM), holds the potential to transform modern medical practice. While significant efforts have been made to enhance genomics education among healthcare professionals and explore the perspectives of various stakeholders, the understanding of patients’ views on PGx remains relatively limited.MethodsHere we present findings from a cohort of 201 patients with various psychiatric illnesses enrolled in the PREPARE prospective PGx study, aiming to investigate their opinions and perceptions regarding the clinical adoption of PGx.ResultsAlthough, 84% of respondents demonstrated a low level of PGx awareness and available tests, 99.5% strongly agreed that PGx testing reduces the occurrence and severity of adverse drug reactions (ADRs) and improves decision-making for prescribing the most appropriate medication. Furthermore, 42.45% of patients who had previously experienced an ADR were significantly more likely to accept a tailored treatment plan based on physician guidance (p < 0.001), compared to 27.37% of those without ADRs.DiscussionCollectively, our data highlights the need for enhanced patient education and awareness about PGx testing and reflects an overall positive patient attitude towards genome-guided therapeutics.